2018
DOI: 10.1016/j.beth.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Body Image–Acceptance and Action Questionnaire–5: An Abbreviation Using Genetic Algorithms

Abstract: Body image concerns are typically linked with negative outcomes such as disordered eating and diminished well-being, but some people can exhibit psychological flexibility and remain committed to their valued goals despite being dissatisfied about their bodies. Such flexibility is most frequently measured by the Body Image-Acceptance and Action Questionnaire (BI-AAQ). This study used a recently validated, fully automated method based on genetic algorithms (GAs) on data from an American community sample (N=538, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 80 publications
2
39
0
1
Order By: Relevance
“…As described earlier, the algorithm first generated a population of shorter scales by randomly sampling items from the full scale. We chose a population size of 200 short scales based on recommendations from previous authors (Basarkod et al, 2018;Sahdra et al, 2016;Yarkoni, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As described earlier, the algorithm first generated a population of shorter scales by randomly sampling items from the full scale. We chose a population size of 200 short scales based on recommendations from previous authors (Basarkod et al, 2018;Sahdra et al, 2016;Yarkoni, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic algorithms were first introduced to solve pattern recognition problems (e.g., finding the best match for a visual pattern) and to computationally simulate biological 4 SHORT MINDFULNESS MEASURE processes (Holland, 1975). More recently, machine-learning techniques based on genetic algorithms have been used to create reliable and valid shortened measures of personality (Yarkoni, 2010), values (Sandy et al, 2014), psychopathy (Eisenbarth, Lilienfeld, & Yarkoni, 2015), experiential avoidance (Sahdra et al, 2016), and body image-acceptance (Basarkod et al, 2018). These algorithms function via principles of evolution and natural selection (Yarkoni, 2010).…”
Section: Genetic Algorithm Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, out of the 1800 participants, 500 answered the flourishing and experiential avoidance questionnaires, and 1262 answered the psychological distress and nonattachment questionnaires. The data related to body image measures are not relevant to this study and are reported elsewhere (Basarkod, Sahdra, & Ciarrochi, 2018).…”
Section: Methodsmentioning
confidence: 99%